An Analysis of Distance Learners' Technological Competence on Moodle-Based Learning Experiences - Ardiasih, Lidwina Sri; Meylina, Meylina; Rahmiaty, Rahmiaty (Faculty of Education Universitas Negeri Malang, 2023)
The purposes of this paper were to describe distance learners’ Moodle-based learning experiences during the Covid-19 pandemic and to analyze distance learners’ technological competence through Moodle-based learning experiences. This study used qualitative method to characterize and analyze the digital competence required to maximize the usage of the Moodle platform as a course media. The questionnaire and Focus Group Discussion (FGD) were used in collecting the data. The total of 509 participants responded to the survey and 17 participants were participated in FGD. The results reveal that the students experienced several obstacles in participating in online learning using the Moodle platform. especially for students who live in remote areas, there are many obstacles; starting from the difficulty of getting an internet connection, data limitations due to having to take many courses, and lack of motivation in completing assignments. Furthermore, the findings also show that students have a fairly high level of technological competence. The paper figures out the digital competences owned by the students in facing new tools and exploiting the technological potentials in a flexible way. This study is crucial due to the important of helping students to understand online learning goals which in turn might increase their primary knowledge, technological usage and behaviors. Furthermore, it is also important for institutions to prepare clear policies to develop their learning systems.